Penggunaan Pendekatan Personal untuk Menghubungkan Usaha Mikro “Wan Alan Padang Panjang” dan Target Pasarnya - Vima Tista Putriana; Yurniwati Yurniwati; Elda Simitra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
A micro business of Wan Alan Padang Panjang, a partner in this community service activity, faces a significant problem: a low sales rate. Wan Alan produces four essential ingredients for cooking (white, red and yellow ingredients and onion paste) and ingredients for making Rendang – the traditional food of West Sumatera. The activity is done through seven steps, i.e. getting to know the partner, becoming users of the partner’s products, understanding characteristics and values of the partner’s products, identifying the right target market, choosing the most effective marketing method, designing promotion strategies and taking advantages of a personal network to introduce the partner’s product. The intervention has resulted in (i) the partner’s products are started to become known by the target market, (ii) an increase in sales gradually, (iii) products have been sold in another city (i.e. Padang), and (iv) three persons are acting as resellers now.